Demographic Profile, Clinical and Analysis of Osteoarthritis Patients in Surabaya - Ilham Wildan Ahmad; Lita Diah Rahmawati; Teddy Heri Wardhana (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Osteoarthritis is a degenerative joint disease which affects joint cartilage. As many as 80% patients movement are limited and 25% of them can not even perform daily activities. Osteoarthritis is one of the ten most disabling diseases in developed countries. Due to its chronic and progressive nature, socio-economic impacts in many developed and developing countries are enormous. The purpose of this study is to determine the profile of patients with osteoarthritis in the Orthopedic Department of RSUD Dr. Soetomo Surabaya (Dr. Soetomo General Hospital)Method: This is descriptive observasional research. Questionnaires data were obtained from all patients in the Department of Trauma and Orthopedic of RSUD Dr. Soetomo Surabaya during September 1, 2016 until October 31, 2016. Thirty five subjects with osteoarthritis were analyzed for the study. The variables observed in the patient profile include sex, age, body mass index, type of osteoarthritis, Kellgren-Lawrence scoring system, and knee osteoarthritis severity index.Result: The result shows that 43% of the samples were aged 60-69 years, 83% of the samples were female, 37% of the samples had an I BMI obesity, 60% of samples had bilateral osteoarthritis, and 77% of samples from primary osteoarthritis. A total of 15 of 53 knee samples had class III, and 15 of 53 knee samples also had class I, and as many as 21 of the 35 samples had a